Modeling neurodegenerative diseases with brain organoids: from development to disease applications - Larriba-González, Teresa; García-Martín, Marina; Ojeda-Hernández, Doddy Denise; Rincón-Cerrada, Paula; Martín-Blanco, Lucía; Benito-Martín, María Soledad; Selma-Calvo, Belén; Fuente-Martín, Sarah de la; Matias-Guiu, Jordi A; Matias-Guiu, Jorge; Gómez-Pinedo, Ulises (Frontiers in Cell and Developmental Biology, 2025)
Organoids derived from stem cells have significantly advanced disease modeling, particularly in neurodegenerative disorders, while advancing personalized and regenerative medicine. These three-dimensional structures reproduce key aspects of human brain organization and functionality, while remaining simplified models that do not yet recapitulate full neural circuitry or disease progression, providing an improved platform for studying disease mechanisms, drug responses, and potential therapeutic strategies. This review explores the methodologies used in organoid development, including the differentiation of stem cells and culture techniques that enable the formation of self-organizing tissues. Organoids have been successfully used to model key cellular and molecular aspects of neurodegenerative diseases such as Alzheimer’s and Parkinson’s, offering insights into early disease mechanisms and potential novel treatment strategies. Key findings highlight that organoids provide more physiologically relevant data than traditional two-dimensional cultures and animal models, making them valuable tools for preclinical research and personalized treatment approaches. However, challenges remain, including variability in organoid generation, lack of vascularization, and difficulties in large-scale production for clinical applications. For the effective integration of organoids into biomedical and clinical applications, future research should prioritize improving reproducibility, standardization, and vascularization methods. Addressing these limitations will enhance their translational potential, leading to more effective treatments for neurodegenerative disorders and broader applications in precision medicine.